Novel P-Solubilizers from Calcium Bound Phosphate Rich Pine Forest of Lower Himalaya. Issue 2 (7th February 2017) - Nazir, Rashid; Hayat, Waseem; Rehman, Palwasha; Iqbal, Akhtar; Irshad, Usman
ABSTRACT: Phosphorus, an essential element for life, is continuously depleting from soils and thus demands sustainable management particularly in agriculture and forestry. Inorganic P constitutes the major proportion as tricalcium phosphate in soils of lower Himalayan region of Pakistan. We sampled these soils and screened for P-solubilizing microbes. A range of culturable microbial community (bacteria and fungi) was isolated and molecularly characterized which make the P available from mineral phosphates. There was an increase in abundance of phosphate solubilizing bacteria (PSB) at a 6-inch depth of the pine rhizosphere compared to the surface soil samples. Moreover, the isolates from lower Himalaya have higher abundance and better efficiency to solubilize the inorganic P than the ones from non-Himalaya. Most likely the P-solubilization done by our P-solubilizing microbes is via acidification as we observed the decrease in pH of the medium of microbial growth. Furthermore, the majority of isolated PSB belong to gammaproteobacterial class of Gram negative bacteria. Most interestingly, 13% of our isolated PSB were psychrotolerant (physiologically active at cold environment, i.e., 4°C) and able to solubilize inorganic P as efficiently as at ambient temperature. This study is unique in reporting the P-solubilizing microbes, particularly the psychrotolerant bacterial strains, of Lower Himalaya. Therefore the isolated bacterial and fungal strains have potential and may serve as biofertilizers in the region to increase the P availability in soils.